2021
DOI: 10.1155/2021/8244000
|View full text |Cite
|
Sign up to set email alerts
|

Approximations of Tangent Polynomials, Tangent –Bernoulli and Tangent – Genocchi Polynomials in terms of Hyperbolic Functions

Abstract: Asymptotic approximations of Tangent polynomials, Tangent-Bernoulli, and Tangent-Genocchi polynomials are derived using saddle point method and the approximations are expressed in terms of hyperbolic functions. For each polynomial there are two approximations derived with one having enlarged region of validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Remark 2.4. Taking λ = 1, Theorem 2.1 and Theorem 2.3, respectively, will give uniform approximationformula and an asypmtotic expansion with enlarged region of validity which are same formulas as those obtained in [17] for the tangent polynomials.…”
Section: Asymptotic Expansions Of Apostol-tangent Polynomialsmentioning
confidence: 63%
“…Remark 2.4. Taking λ = 1, Theorem 2.1 and Theorem 2.3, respectively, will give uniform approximationformula and an asypmtotic expansion with enlarged region of validity which are same formulas as those obtained in [17] for the tangent polynomials.…”
Section: Asymptotic Expansions Of Apostol-tangent Polynomialsmentioning
confidence: 63%
“…This validity can be enlarged by isolating the contribution of the poles. This method was done in [4], [5]. The authors recommend to obtain approximation formulas with enlarged region of validity for the polynomials studied here.…”
Section: Comparing Coefficients Yieldsmentioning
confidence: 99%
“…Asymptotic approximations for higher order Genocchi polynomials using residues were done in [2] and [3]. Approximations for the Bernoulli and Euler polynomials using hyperbolic functions were obtained in [4] and approximations for Genocchi polynomials in terms of hyperbolic functions were obtained in [5]. At the time of the search, there were no approximations for the generalized Apostol-Bernoulli, Apostol-Euler and Apostol-Genocchi polynomials found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Corcino et al produced related studies on asymptotic approximations of some special polynomials in terms of hyperbolic functions (see [10][11][12]). It is observed that there is a resemblance in the generating function of the Apostol-tangent polynomials in [10] and the Apostol-Frobenius-Euler polynomials.…”
Section: Introductionmentioning
confidence: 99%